Efek Ekstrak Buah Belimbing Wuluh terhadap Kadar SOD Paru Tikus yang Dipapar Asap Rokok: Effect of Starfruit Extract on SOD Levels in the Lungs of Rats Exposed to Cigarette Smoke - Setyaningsih, Anggun Try; R. Susanti (Universitas Negeri Semarang, 2025)
Cigarette smoke contains a variety of chemical compounds that are harmful to more than 4000 particles that are particularly harmful to cell metabolism such as tar, nicotine, and CO. Cigarette smoke is a free radical that can cause oxidative stress if excessively inhaled in the lungs. Oxidative stress can be characterized by a decrease in SOD levels. SOD enzymes are naturally occurring antioxidants produced in the body to neutralize free radicals. This study aims to find out the effect of Averrhoa bilimbi fruit extract on the lung SOD level of male rats exposed to cigarette smoke. This study used 25 male rats divided into five groups, namely the normal (K) group, the negative group given exposure to cigarette smoke (K-), the treatment group given exposure to cigarette smoke and the extract A. bilimbi fruit 3 mg/kgBB (K1), treatment group given exposure to cigarette smoke and fruit extract A. bilimbi 6 mg/kgBB (K2), treatment group given exposure to cigarette smoke and fruit extract of A. bilimbi 12 mg/kgBB (K3). The antioxidant content of the A. bilimbi fruit extract is analyzed using the DPPH method and the SOD level of the lungs is measured by the calorimetric method. Analysis of SOD data using One Way Anova test and LSD test. The results of the antioxidant test of the A. bilimbi fruit extract showed a 23.37% antioxidant status. The results of statistical tests of A. bilimbi fruit extract on lung SOD levels exposed to cigarette smoke have a real effect. Each group showed real differences in the form of K (79.99%), K- (21.07%), K1 (52.14%), K2 (64.29%), K3 (72.86%). From the results of the research that has been carried out, it can be concluded that the fruit extract of A. bilimbi has an effect on the increase in the SOD level of mice exposed to cigarette smoke.